Efficacy of a new strength training design: the 3/7 method - Stragier, S.; Baudry, S.; Carpentier, A.; Duchateau, J. (European Journal of Applied Physiology, 2019)
Aim: This study investigated the efficacy of a new strength training method on strength gain, hypertrophy, and neuromuscular fatigability. Methods: The training exercise consisted of elbow flexion against a load of ~ 70% of one repetition maximal (1RM). A new method (3/7 method) consisting of five sets of an increasing number of repetitions (3 to 7) during successive sets and brief inter-set intervals (15 s) was repeated two times after 150 s of recovery and compared to a method consisting of eight sets of six repetitions with an inter-set interval of 150 s (8 × 6 method). Subjects trained two times per week during 12 weeks. Strength gain [1RM load and maximal isometric voluntary contraction (MVC)], EMG activity of biceps brachii and brachioradialis, as well as biceps` brachii thickness were measured. Change in neuromuscular fatigability was assessed as the maximal number of repetitions performed at 70% of 1RM before and after training. Results: Both 3/7 and 8 × 6 methods increased 1RM load (22.2 ± 7.4 and 12.1 ± 6.6%, respectively; p < 0.05) and MVC force (15.7 ± 8.2 and 9.5 ± 9.5%; p < 0.05) with a greater 1RM gain (p < 0.05) for the 3/7 method. Normalized (%Mmax) EMG activity of elbow flexors increased (p < 0.05) similarly (14.5 ± 23.2 vs. 8.1 ± 20.5%; p > 0.05) after both methods but biceps` brachii thickness increased to a greater extent (9.6 ± 3.6 vs. 5.5 ± 3.7%; p < 0.05) for the 3/7 method. Despite subjects performing more repetitions with the same absolute load after training, neuromuscular fatigability increased (p < 0.05) after the two training methods. Conclusion: The 3/7 method provides a better stimulus for strength gain and muscle hypertrophy than the 8 × 6 method.